Barriers to last mile connectivity: The role of crime in metro station accessibility - Kanwar D Singh; Rashmi Ashtt (The Scientific Temper, 2024)
The accessibility of metro stations is a crucial aspect of urban mobility, yet last-mile connectivity often faces significant barriers, particularly due to crime and safety concerns. This study examines the role of crime as a determinant of last-mile connectivity to metro stations, focusing on how criminal activities and the fear of crime influence commuter behavior and accessibility. Through a mixed-methods approach, the research integrates quantitative analysis of crime data around metro stations with qualitative insights from commuter surveys and interviews with urban planners and law enforcement officials. The findings reveal that higher crime rates and perceived safety risks significantly reduce commuters' willingness to use metro systems, particularly during early morning and late evening hours. This reduced accessibility not only hampers the efficiency of metro systems but also exacerbates issues related to traffic congestion, environmental pollution, and social inequality. The study further explores the economic impact of crime on areas surrounding metro stations, highlighting how declining property values and business activity contribute to a cycle of disinvestment and increased crime. To address these challenges, the study suggests a comprehensive approach combining enhanced surveillance, improved lighting, community engagement, and urban design interventions. These strategies are critical for creating safer, more accessible environments that encourage the use of public transportation and promote sustainable urban development. The research provides valuable insights for urban planners, policymakers, and scholars interested in improving last-mile connectivity and enhancing the overall quality of urban life.